PELATIHAN HOME INDUSTRI SAYURAN BAYEM UNTUK DIJADIKAN MAKANAN KHAS DI DESA BAYEMGEDE KEC. KEPOHBARU - Sarah Ocdi Melanda; Yeni Mahmudah; Sulhatul Habibah; Mahbub Junaidi (LPPM Universitas Islam Darul 'Ulum Lamongan, 2021)
This training was given to the participants with the aim of increasing the participants' skills on matters relating to the processing of vegetables into food, namely steamed spinach cakes. The material presented and the method of delivering the material will be the main attraction of the participants to achieve the desired target in this activity. Submission of material accompanied by direct practice is the right method to do, where from the results of the questionnaire 100% of the participants understand the training material presented.